Comprehensive Analysis of the Composition of Seed Cake and its Fatty Oil from Swietenia mahagoni Jacq. Growing in Bangladesh - Mostafa, M; Jahan, Ismet Ara; Riaz, M; Hossain, Hemayet; Nimmi, Ishrat; Miah, A Sattar; Chowdhury, JU (Dhaka University Journal of Pharmaceutical Sciences, 2012)
The proximate nutritional compositions of Swietenia mahagoni Jacq seed cake and the fatty acids present in the oil were investigated. The proximate nutritional composition of the seed cake were analyzed by the standard methods and it was found to contain moisture (14.37%), minerals (16.36%), fats (19.42%), crude fiber (19.60%), protein (8.76%) and carbohydrate (21.49%). The fatty acid composition of the oil was analyzed by GC-MS and a total of 48 compounds have been identified. The major constituents of the methylated fatty esters were linoleic acid (26.00%), elaidic acid (24.39%), stearic acid (14.32%), palmitic acid (12.97%), 10-methyl-10-nonadecanol (5.24%), ecosanoic acid (2.48%), 3-heptyne-2,5-diol, 6-methyl-5-(1-methylethyl) (2.03%), octadecanoic acid 9,10,12-trimethoxy (1.90%); 1,3-dioxalane, 4 ethyl-4-methyl-2-pentadecyl (1.89%) and 2-furapentanoic acid (1.03%). It is evident from this study that the oil can be considered as a good source of unsaturated fatty acids. DOI: http://dx.doi.org/10.3329/dujps.v10i1.10015 DUJPS 2011; 10(1): 48-52